Schools Without Failure 1977. Glasser's Approach to Discipline--Realistic and Working - Glasser, William ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
Glasser presents the ten-step approach to school discipline based on his concept of Reality Therapy, discusses preliminary results of implementation of this approach, and then presents the results of a recent survey. Surveyed were 24 schools--14 elementary, five junior high schools, and five high schools--chosen to give a representative picture of education in this country. Summative statements of each of the 11 questions are presented. The questions deal with the success of the method, the changes each school made in the approach, and the effects the program had on the school. (IRT)
ERIC Note: Paper presented at the Annual Meeting of the American Association of School Administrators (109th, Las Vegas, Nevada, February 25-28, 1977).
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Discipline; Elementary Secondary Education; Models; Program Descriptions; Questionnaires; School Surveys; Student Behavior; Students; Suspension; Reality Therapy; Speeches/Meeting Papers